DEVELOPMENT OF OUTDOOR LEARNING TO IMPROVING LEARNING OUTCOMES REVIEWED FROM ABSTRACT THINKING ABILITY, RESPONSE TO GUIDELINES AND SCIENCE PROCESS SKILLS FOR STUDENT OF VOCATIONAL HIGH SCHOOLS - Sukisna Sukisna; Suparwoto Suparwoto (Universitas Muhammadiyah Mataram, 2020)
Abstract: This study aims to (1) describe the feasibility of outdoor learning models, (2) describe the developed outdoor learning models that can improve student learning outcomes, (3) describe whether abstract thinking abilities, responses to guidance and science process skills can contribute to understanding resistivity topic in vocational schools.This research was conducted using the Research and Development method with 4D, namely define, design, develop, and disseminate. The subjects of this study were of 49 students of class X TKPI. The research sample consisted of one experimental class and one control class. Learning outcomes data obtained from the posttest, abstract thinking ability data obtained from abstract thinking test questions, science process skills data obtained from science process skills test questions, response data to learning were collected by questionnaire—data analysis using ANCOVA analysis. The results showed that (1) the development of learning devices with the topic of types of obstacles meet the feasible criteria, (2) there is a positive influence of outdoor learning in improving student learning outcomes indicated by the value of Fcount = 32.41 while Ftable 5% = 2.81. The difference in learning outcomes shown by the gain index of the experimental class 0.78 and the control class 0.67, (3) there is a relationship between the ability to think abstractly, responses to learning and science process skills with student learning outcomes in the topic of resistivity that can be seen from the regression coefficient R = 0.8268 and the coefficient of determination R2 = 0.6836. So that it can be interpreted that the three covariates are good predictors of learning outcomes, (4) the effective contribution of abstract thinking ability 1.908%, (5) the relative effective contribution of science process skills 51.269%, (6) effective contribution of responses to effective learning 1,076%. Abstrak: Penelitian ini bertujuan untuk (1) mendeskripsikan kelayakan model pembelajaran outdoor learning, (2) mendeskripsikan model pembelajaran outdoor learning yang dikembangkan dapat meningkatkan hasil belajar siswa, (3) mendeskripsikan apakah kemampuan berfikir abstrak, tanggapan terhadap bimbingan dan keterampilan proses sains dapat memberikan kontribusi terhadap pemahaman hambatan jenis di tingkat SMK. Penelitian ini dilakukan dengan metode Reseacrh and Development dengan 4D yaitu define, design, develop dan disseminate. Subjek penelitian ini adalah 49 siswa kelas X TKPI SMK. Sampel penelitian terdiri dari satu kelas eksperimen dan satu kelas kontrol. Data hasil belajar diperoleh dari posttest, data kemampuan berfikir abstrak didapatkan dari soal test berfikir abstrak, data keterampilan proses sains didapatkan dari soal test keterampilan proses sains, data tanggapan terhadap pembelajaran dikumpulkan dengan angket. Analisis data menggunakan analisis anakova. Hasil penelitian menunjukkan bahwa (1) pengembangan perangkat pembelajaran dengan topik hambatan jenis memenuhi kriteria layak, (2) terdapat pengaruh positif pembelajaran outdoor learning dalam meningkatkan hasil belajar siswa ditunjukkan oleh nilai Fhitung = 32,41 sedangkan Ftabel 5% = 2,81. Perbedaan hasil belajar ditunjukkan oleh indeks gain kelas eksperimen 0,78 dan kelas kontrol 0,67, (3) terdapat hubungan antara kemampuan berfikir abstrak, tanggapan terhadap pembelajaran dan keterampilan proses sains dengan hasil belajar siswa topik hambatan jenis yang dapat dilihat dari koefisien regresi R = 0,8268 dan koefisien determinasi R2 = 0,6836 sehingga dapat diartikan ketiga kovariat merupakan prediktor yang baik untuk hasil belajar, (4) sumbangan efektif kemampuan berfikir abstrak 1,908 %, (5) sumbangan efektif relatif keterampilan proses sains 51,269%, (6) sumbangan efektifn tanggapan terhadap pembelajaran efektifnya 1,076 %.